Emergency bedside ultrasound-benefits as well as caution: Part 2. Issue 6 (December 2019) - Godement, Mathieu; Malbrain, Manu L.N.G.; Vieillard-Baron, Antoine
Abstract : Purpose of review: Critical care echocardiography (CCE) has become an important component of general critical care ultrasonography, and a current review of its performance is presented. Recent findings: Basic CCE should be performed as a goal-directed examination to better identify specific signs and to answer important clinical questions concerning acute hemodynamic concerns. It has evolved in the ICU and also in the emergency department not only for improved diagnostic capability but also as an effective part of the triage process. It remains an efficacious procedure even in patients with respiratory failure when combined with lung ultrasonography. Numerous acronyms were proposed, but in all cases, CCE responds to the same rules as fundamental echocardiography. Basic CCE requires accessible and comprehensive training for physicians and is mandatory for all intensivists. Development of pocket echo devices may increase the use of basic CCE as has miniaturization of other medical technologies. Performance should be managed by guidelines, and the CCE training program should be standardized worldwide. More trials are welcome to evaluate its impact on patient outcomes. Summary: Thanks to its ability to quickly obtain a diagnostic orientation at the bedside and to implement targeted therapy, basic CCE over the past decade has become an essential tool for hemodynamic assessment of the cardiopulmonary unstable patient. Its more recent incorporation into the education of trainees in medical school and residencies/fellowships has reinforced its perceived importance in critical care management, despite the relative paucity as yet of rigorous scientific evidence demonstrating positive outcome modification from its use.